IMPLEMENTATION OF LAW NO 4 OF 2019 CONCERNING MIDWIFE IN THE BENEFITS OF MARYAM GYSMS IN PREGNANCY DURING PANDEMIC - Fitriana, Yuni; Revika, Era; Winarsih, Winarsih (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2022)
Abstract: The COVID-19 pandemic for pregnant women is not held in health services. During a pandemic, pregnant women often experience anxiety that affects childbirth. Maryam gymnastics can be done to overcome pregnancy complaints. This study aims to analyze the perceptions, motivations, benefits and movements of Maryam's gymnastics that are felt comfortable. Qualitative inductive research method (phenomenological study). The sample of this study was 26 pregnant women TM II and TM III. The analysis was triangulated. The results of the Perceptions of Maryam's Gymnastics research are pregnancy exercises based on the events of Mother Mary during the birth of Prophet Isa As there are prayer movements (rukuk, sitting Tawaruk and prostration) and dhikr. Maryam gymnastics provides psychological and spiritual health for the mother. The motivation for participating in Maryam's Gymnastics is for a fast, natural delivery and a healthy fetus in the midst of a pandemic according to Islamic rules, successful VBAC (Vaginal Birth After Cesarea), eliminating muscle stiffness that causes back and pelvic pain, practiced during prayer and spiritually before delivery, adding friendships, prevent the transmission of covid 19 because it is carried out online. Maryam's gymnastics is beneficial for blood circulation, reduces anxiety and stress, increases energy, improves mood, reduces discomfort, relaxes the body, reduces digestive disorders, increases energy, overcomes insomnia, reduces cramps and swollen feet, mind and heart draws closer to Allah. , being productive in carrying out activities, accelerating the birth process, managing pain into happiness and pleasure, praying more earnestly, being happy when prayer arrives because it is also exercise. The most comfortable movements are almost all movements of Maryam's gymnastics, bowing, sitting, reciting, prostration, and breathing exercises. Maryam's gymnastics is one of the efforts to improve the health of pregnant women and the implementation of Law No. 4 of 2019 concerning Midwifery.Abstrak: Pandemi COVID-19 kelas ibu hamil tidak diselenggarakan di pelayanan kesehatan. Dimasa pandemic ibu hamil sering mengalami kecemasan yang berpengaruh terhadap persalinan. Senam Maryam dapat dilakukan untuk mengatasi keluhan kehamilan. Penelitian bertujuan menganalisa persepsi, motivasi, manfaat dan gerakan senam Maryam yang dirasakan nyaman. Metode penelitian induktif kualitatif (studi fenomenologi). Sampel penelitian ini 26 Ibu Hamil TM II dan TM III. Analisa dilakukan triangulasi. Hasil penelitian Persepsi Senam Maryam adalah senam hamil berlandaskan kejadian bunda maryam saat melahirkan Nabi Isa As terdapat gerakan sholat (rukuk, duduk tawaruk dan sujud) serta dzikir. Senam maryam memberikan kesehatan secara psikologi dan rohani ibu. Motivasi mengikuti Senam Maryam yaitu agar persalinan cepat,alami serta janin lahir sehat ditengah pandemic sesuai kaidah islam, berhasil VBAC (Vaginal Birth After Cesarea), menghilangkan kekakuan otot-otot penyebab nyeri punggung dan panggul, dipraktekkan saat sholat juga ruhiyah menjelang persalinan, menambah pertemanan, mencegah penularan covid 19 karena dilaksanakan online. Senam Maryam bermanfaat melancarkan sirkulasi darah, mengurangi kecemasan dan stress, meningkatkan energi, suasana hati membaik, mengurangi ketidaknyamanan, tubuh rileks, mengurangi gangguan pencernaan, meningkatkan energi, mengatasi sulit tidur, mengurangi kram dan bengkak kaki, pikiran dan hati semakin mendekatkan diri kepada Allah, menjadi produktif menjalani aktivitas, mempercepat proses bersalin, mengelola rasa sakit menjadi kebahagiaan dan kesenangan , sholat lebih kusyuk, senang saat sholat tiba karena sekaligus senam. Gerakan paling nyaman yaitu hampir semua gerakan senam maryam, gerakan rukuk, duduk tawaruk, sujud, gerakan melatih napas. Senam Maryam ini menjadi salah satu upaya meningkatkan kesehatan ibu hamil serta implementasi Undang-undang nomor 4 tahun 2019 tentang Kebidanan.